2018
DOI: 10.3389/fmicb.2018.00103
|View full text |Cite
|
Sign up to set email alerts
|

Peptidoglycan Recognition Protein 3 Does Not Alter the Outcome of Pneumococcal Pneumonia in Mice

Abstract: Pneumococci frequently cause community-acquired pneumonia, a disease with high mortality rates, particularly in young children and in the elderly. Endogenous antimicrobial peptides and proteins such as PGLYRP3 may contribute to the progression and outcome of this disease. Since increasing antibiotic resistant strains occur all over the world, these endogenous antimicrobial molecules are interesting new targets for future therapies. In this study, the expression pattern of PGLYRP3 was analyzed in alveolar epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Mice were routinely analyzed for the genotype as described previously (Saha et al, 2009; Shrivastav et al, 2018). Briefly, tail tips were digested overnight in Tris-EDTA-SDS buffer and Proteinase K (Sigma-Aldrich, St. Louis, MO, United States).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Mice were routinely analyzed for the genotype as described previously (Saha et al, 2009; Shrivastav et al, 2018). Briefly, tail tips were digested overnight in Tris-EDTA-SDS buffer and Proteinase K (Sigma-Aldrich, St. Louis, MO, United States).…”
Section: Methodsmentioning
confidence: 99%
“…For isolating PMNs, the femurs and tibiae of mice were flushed with PBS, and cells were filtered through a 70 μm cell strainer as described earlier (Shrivastav et al, 2018). PMNs were then positively isolated using the mouse anti-Ly6G MicroBead kit (Milteny Biotec GmbH, Telterow, Germany) according to manufacturer’s instruction, seeded in RPMI1640 containing 2% FCS and 1% Glu and infected immediately.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The higher mortality of KLF4 -/mice in comparison to KLF4 +/+ mice during S. pneumoniae induced pneumonia are in line with the findings from Shen et al: they had reported earlier that KLF4 KO mice have lower survivability with respect to WT mice after infection with E. coli 166 . Previous reports have described that in order to understand the progression of pneumococcal pneumonia in a murine model, the mice have to be monitored 10 days after infection 177,229 . It has already been reported that various clinical symptoms associated with infection in mice include fall in body temperature, less responsiveness, dyspnea 230 .…”
Section: In Vivomentioning
confidence: 99%